Review of Contemporary Economic Jurisprudence Against Cooperation Agriculture : Study Cooperation Farming in Lumbush Bapereng Tanah Datar District - Rahmawita .; Zainuddin . (JOURNAL OF SHARIA ECONOMICS, 2023)
This study aims to examine the contemporary economic jurisprudence review of agricultural cooperation carried out by farmers in Jorong Lumburan Bapereng . As the focus of this research, several research questions were formulated: how is the implementation and forms of agricultural cooperation in Jorong Lumburan Bapereng . After the data is found, it is then discussed using the relevant theory . This research uses a qualitative method with a qualitative descriptive design. Data obtained through interviews with owner land And cultivator . Study This find that implementation cooperation agriculture with method deliver fully to cultivator until harvest . Form of cooperation with system profit sharing, while the seeds, fertilizers and other costs are borne by the farmers . From sight jurisprudence economy implementation And form of cooperation this is similar to mukhabarah . It's just that from an implementation point of view there are things that have the potential to cause unilateral losses , because the land owner fully surrenders to the farmer cultivating the land until harvest